The Effect Of Transformational Leadership Style, Organizational Culture, And Competence On Job Satisfaction With Compensation As An Intervening Variable: Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi, Dan Kompetensi Terhadap Kepuasan Kerja Dengan Kompensasi Sebagai Variabel Intervening - Risky Andrianto; Slamet Harjatno (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to examine the effect of transformational leadership style, organizational culture, and competence on job satisfaction with compensation as an intervening variable. This research is a descriptive study using quantitative methods. The sample used in this study amounted to 95 respondents using a saturated sampling method. The data collection technique used a questionnaire with a Likert scale. This study uses SEM analysis. Based on the results of research with a hypothesis testing variables transformational leadership style, organizational culture, and competence on job satisfaction with compensation as an intervening variable. From the PLS test results, it is known that transformational leadership style has a direct effect on job satisfaction, Organizational Culture has a direct effect on job satisfaction, Competence has a direct effect on job satisfaction, Transformational leadership style has a direct effect on Compensation, Organizational Culture has a direct effect on Compensation, Competence has a direct effect on Compensation and Transformational leadership style, organizational culture and competence have an effect on job satisfaction through compensation.